Is Something Really Wrong with Macroeconomics? - Ricardo Reis (Center for Economic Studies and ifo Institute (CESifo), 2017)
While there is much that is wrong with macroeconomics today, most critiques of the state of macroeconomics are off target. Current macroeconomic research is not mindless DSGE modelling filled with ridiculous assumptions and oblivious of data. Rather, young macroeconomists are doing vibrant, varied, and exciting work, getting jobs, and being published. Macroeconomics informs economic policy only moderately and not more nor all that differently than other fields in economics. Monetary policy has benefitted significantly from this advice in keeping inflation under control and preventing a new Great Depression. Macroeconomic forecasts perform poorly in absolute terms and given the size of the challenge probably always will. But relative to the level of aggregation, the time horizon, and the amount of funding, they are not so obviously worse than those in other fields. What is most wrong with macroeconomics today is perhaps that there is too little discussion of which models to teach and too little investment in graduate-level textbooks.
Keywords: E00; 330